Epidemiology of neonatal disorders attributable to low birthweight-global burden of disease research, 1990–2021 - Zhang, Qi; Luo, Lan; Yan, Lai-lai; Guo, Jing; Wu, Hui-jun; Zhang, Zi-wei; Zhu, Yu-hua; Qiao, Rui (Frontiers in Pediatrics, 2025)
BackgroundTo evaluate global, regional, and national trends in the burden of neonatal diseases attributable to LBW, as well as associated health inequalities, from 1990 to 2021.MethodsUsing data from the Global Burden of Disease Study (GBD2021), we analyzed deaths and DALYs due to LBW-attributable neonatal diseases. Data were stratified by gender, geographic region, epidemiological characteristics, and SDI levels. Trends and influencing factors were investigated through Joinpoint regression, health inequality analysis, and frontier modeling.ResultsIn 2021, the global age-standardized mortality rate (ASMR) and age-standardized disability-adjusted life year (DALY) rate (ASDR) for neonatal diseases associated with low birth weight (LBW) were 22.76 [95% uncertainty interval (UI): 19.63–26.40] and 2,227.54 (95% UI: 1,939.96–2,563.52) per 100,000, respectively. Over the past 32 years, these rates have consistently declined, with average annual percentage changes (AAPCs) of −1.40 [95% confidence interval (CI): −1.48 to −1.33] for ASMR and −1.27 (95% CI: −1.34 to −1.21) for ASDR. Notably, absolute health inequality related to the Socio-demographic Index (SDI) has decreased, as indicated by a reduction in DALY disparities between the most and least developed countries from −4,216.49 (95% CI: −4,558.27 to −3,874.71) in 1990 to −2,635.35 (95% CI: −2,868.40 to −2,402.30) in 2021. However, relative health inequality has worsened, with the relative disease burden in low-SDI countries increasing from −33.46% (95% CI: −36.29% to −30.63%) to −40.20% (95% CI: −44.02% to −36.39%). The burden of neonatal diseases remains disproportionately concentrated in low-SDI regions. Frontier analyses highlight opportunities for improvement across development levels. Some low-SDI countries have achieved minimal theoretical disease burdens, whereas certain high-SDI countries lag in reducing their neonatal disease burdens.ConclusionOver the past 32 years, the global burden of neonatal diseases attributable to LBW has significantly decreased, but inequality in disease burden has intensified. Addressing this disparity requires sustained international and governmental efforts to improve the accessibility, equality, and quality of healthcare for pregnant women and newborns.